Manual de cosecha y poscosecha de pitahaya amarilla (Hylocereus megalanthus) - Yoplac, Ives Julian; Chávez Santos, River; Santos Peláez, Julio César (Instituto Nacional de Innovación Agraria, 2021)
62 páginas